(3JMbjb efGRd GdbeQs - (3GHf agO Ydj eMeO GdMdjs
(3ChdgG (B:s
(3GdMeO ddg GdMi GdOGFe Gdbjhe LGYd GdCadGc ddYGde cGdQbhe hHYO abO HjfJ ai gPg GdebGdI edNU eG PcQg GdChGFd s
(3BNQgG (B:s
(3jfbi GdHdZe hjbWY QGFMI Gdae hdjcf gPG BNQ eG fhQOg ai gPG GdHGH hGdMeO ddg Ydi GdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdeLGejYs